APPLICATION OF LINEAR PROGRAMMING IN OPTIMIZING PRODUCTION COMBINATIONS TO MAXIMIZE PROFITS: A STUDY ON MEATBALL SHOP IN WEST BANDUNG REGENCY - Ismail, Ade; Laela, Ela (NIAGAWAN, 2024)
Optimization of the amount of production to maximize profits is still an obstacle to the growth of MSMEs in Indonesia. This study aims to determine the combination of the production amount of each Bakso Barokah Shop product type and the optimization of the income obtained. A linear program of simplex methods with POM-QM software is then used to obtain accurate research results. Based on the analysis results, the maximum profit per week of Barokah Meatball Shop is IDR 2,700,000, which is six times the production of Mercon meatballs. The calculation results show that the optimal meatball production is to focus on Mercon meatball production rather than other meatballs. The results of this study can be used as a decision-making consideration related to production problems to get optimal profits.